Vardenafil for the treatment of erectile dysfunction: an overview of the clinical evidence - Antonio Martín Morales (Dove Medical Press, 2009)
Antonio Martín Morales1, Vincenzo Mirone2, John Dean3, Pierre Costa41Department of Urology, Hospital Carlos Haya, Malaga, Spain; 2Department of Urology, University Federico II, Naples, Italy; 3St. Peter’s Sexual Medicine, The London Clinic, London, UK; 4Center Hospitalier Caremeau, Nîmes, FranceAbstract: Many men with erectile dysfunction (ED) also have associated underlying cardiovascular and metabolic conditions, for which they are likely to be taking medication. Therefore, cardiovascular safety and potential drug interactions are two of the major concerns when using PDE-5 inhibitors in these patients. The PDE-5 inhibitor, vardenafil, is characterized by a rapid onset of action, increased duration of erection, high rates of first-dose success and reliable efficacy that can be maintained with continued use. In both clinical trials and real-life observational studies, vardenafil has demonstrated a favorable efficacy and safety profile in men with ED, including those with associated underlying conditions such as diabetes, hypertension and dyslipidemia. Importantly, the concomitant use of medication for these conditions is not associated with any noteworthy changes in the efficacy and safety of vardenafil. The evidence presented in this review supports the use of vardenafil as a first-line treatment for men with ED, including those with underlying conditions.Keywords: vardenafil, erectile dysfunction, efficacy, safety, underlying conditions